Menyokong Pertanian Terpadu Berkelanjutan melalui Pemanfaatan Limbah Buah Jeruk Siam Banjar Menggunakan Dekomposter Ember Tumpuk: Supporting Sustainable Integrated Agriculture by Utilizing Siam Banjar Orange Fruit Waste Using a Stacked Bucket Decomposter - Syawalluna, Andini Putri; Nabila, Ardelia; Satrianto, Daniel; Hafidzah, Fadia Audyani; Farid, Muhammad Miftah; Saputra, Riza Adrianoor (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This outreach and training activity was carried out by MBKM Fakultas Pertanian ULM Membangun Desa 2024 students as a form of implementing the Tri Dharma Perguruan Tinggi. This outreach and training activity was carried out by MBKM students of the Faculty of Agriculture Building Villages in 2024 as a form of implementation of the Tridharma of Higher Education, namely community service. This activity was held at Al Fattah Islamic Vocational School, Sungai Tuan Ulu Village, Astambul District, Banjar Regency, South Kalimantan. This activity aims to increase the knowledge of the general public, especially the younger generation, about the use of local resources of Banjar Siamese oranges. By carrying out this activity, understanding the use of local resources is expected to reduce the use of synthetic fertilizers to achieve environmental and sustainable agriculture.